The characteristic of dietary supplementation among elderly women - Wojciak, Rafal Wojciech; Cisek-Woźniak, Angelika; Tomczak, Ewa (Journal of Medical Science, 2019)
Aim. There is a growing awareness in Polish society, that a healthy lifestyle and proper nutrition have positively affected in old age. This effect influences the increasing consumption of dietary supplements to improve the health, however sometimes in an uncontrolled way. Taking above together the aim of this preliminary study was to assess the prevalence of the use of dietary supplements in elderly women. Material and Methods. The study was conducted on 95 elderly women aged 65 to 89 years. The participants were asked to complete a questionnaire about their physical activity as well as medicines and supplements intake. Results. Based on the questionnaire, it can be concluded that supplementation was common among the tested group. The most frequently seniors used preparations to assist the circulatory system and diet supplements. They also took this, supporting the work of the intestine, to assist urinary tract and the work of heart. The decision to start of supplementation was most often taken under the influence of television advertisements, pharmacy worker as well as from friends. There were statistically differences in presented results between studying populations according to their age. Conclusions. Important and essential is education of older people, concerning the appropriate use of dietary supplements, to make supplementation safe and distinct improvement in health.